Financing infrastructure construction applying Indonesia syariah finance institutions - Syarief Gerald Prasetya (STIE Binaniaga, 2019)
Since Indonesia is one of the countries having most Moslems in the world, itshould have been able to use Syariah financing to finance the construction to increase people welfare. Aims of this research are to understand the development of Syariah Finance Institutions, development of infrastructure construction in Indonesia and to see the extent of which the contribution of Syariah Finance Institution has been upon the infrastructure construction in Indonesia. Result of the analysis has indicated that total of Syariah Finance Institutions in Indonesia has been increasing each year and its assets has tended to increase accordingly. Infrastructure construction has tendedto elevate in Indonesia, however, it is still beyond other ASEAN countries. Contribution of Syariah Finance Institutions has been getting bigger upon theinfrastructure construction development in Indonesia, but it is still beyond other conventional finance authorities.Keywords: infrastructure, Syariah Finance Institution